PENYEDIAAN FASILITAS PAPAN TULIS, MADING DAN INFORMASI UNTUK PEMBELAJARAN TATAP MUKA MASA PANDEMI DI SMA TRIGUNA 1956 - Mekar Sari Suteja; Nina Carina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
The Covid-19 pandemic has also changed the pattern of learning and the quality of children's education. Many observers of the world of education inspect that the online learning system that has been implemented has caused many negative impacts such as the magnitude of the learning loss of students. This is due to the limited mastery of information technology, facilities, infrastructure, and internet access. After more than a year of a pandemic, on August 24, 2021, the government lowered the PPKM level for the Jabodetabek and Java-Bali cities from level 4 to 3. Reopen direct learning (PTM) is planned to start Monday, August 30, 2021. According to the Joint Decree of the Four Ministers, the PTM that will be implemented will consist of 2 phases, namely a transition period (2 months from the start of PTM) and new habits (after the transition period). This PKM partner, SMA Triguna, is a private high school under the Triguna Foundation which also wants to realize the PTM program in their school. However, the limited income budget is their main problem in procuring health protocol facilities such as the provision of blackboards, madding and information. The PKM implementation process is carried out through the survey stage and board prototype study; The design results review of the collaborative PKM Team with the title